Juridical Review On Process Loading Liability Rights To Land That Has Not Registered In The District Of Semarang - Ika Yulia Ningrum; Anggrin Gayuh Praptiwi; Setyawati Setyawati (Jurnal Akta, 2019)
This study aims to analyze the process of Encumbrances On land that has not been registered in the District of Semarang, Barriers which appeared in the Proceedings Encumbrances On Land Not Yet Enrolled in the District of Semarang and solutions to overcome barriers Appears In The Process Encumbrances On Land Not Yet registered in the District of Semarang.This study uses empirical juridical approach, the approach to reviewing the legislation relating to the issues to be discussed, and also conducted a field approach to obtain information as supporting material. Specifications of this research is descriptive analysis that describes the laws that apply associated with legal theories and practice of positive law concerning these issues.Based on the research results that the implementation of Encumbrances against certified land not yet in practice never done bank by making APHT directly against yangbelum certified lands. Bank in this case was limited to making SKMHT only. Obstacles that arise in the process of loading encumbrance on land that has not been registered in the District of Semarang is when the giver of mortgage has died, a typing error and the installation of the second rank security rights. The solution is under hand sales, writing and checking certificates rectification katas ha of new land.Keywords: Land Registry; Loading Liability Rights, Land That Has Not Registered